Harmonizing Judicial Data Protection Standards Between The EU and US - Azizan, Akmal; Zahra, Salma; Sophia, Sally; Perai, Nurajam (Jurnal Hukum dan Peradilan, 2025)
In the digital age,the protection of personal data has become a crucial issue, often leading to conflicts between regions with differing legal and cultural values. The European Union (EU) and the United States (US) represent a prominent example of such a divergence, with the EU emphasizing stringent data protection measures and the US prioritizing economic and security interests. These differing approaches have resulted in significant challenges for transatlantic data flows, notably highlighted by the invalidation of the EU-US Privacy Shield by the Court of Justice of the European Union (CJEU). This essay aims to explore the complexities of privacy and data protection within the context of transatlantic relations, providing a comprehensive analysis that bridges empirical data and theoretical insights. The study seeks to identify the economic, operational, and legal impacts of regulatory divergences and propose evidence-based policy recommendations to harmonize data protection standards between the EU, and the US. The research employs a literature study method, systematically reviewing scholarly articles, legal texts, case law, and policy documents related to data protection and privacy. It integrates Socio-Legal Theory to analyze the intersection of legal frameworks, social practices, and cultural attitudes. Empirical data is gathered through qualitative and quantitative analysis, focusing on the economic impacts, compliance challenges, and legal risks associated with transatlantic data flows. The findings reveal significant economic costs and compliance burdens for businesses due to the absence of stable data transfer mechanisms. Legal risks and judicial consequences under the EU’s GDPR further exacerbate these challenges. The study identifies specific areas where regulatory harmonization is possible, offering policy recommendations grounded in empirical data to enhance data protection standards and facilitate smoother data exchanges. By combining empirical analysis with theoretical insights, this research contributes to a nuanced understanding of data protection and privacy, essential for informed policy-making and effective judicial practice.